The Development of Mobile Money and the Politics of Financial Inclusion in Tanzania - Mhella, Deogratius Joseph (SOCIAL REVIEW. International Social Sciences Review / Revista Internacional de Ciencias Sociales, 2019)
This paper analyses the development of mobile money in Tanzania and the politics of financial inclusion that enhanced it. Mobile money has played a significant part in reaching the financially unreached and excluded people overtaking banking and other financial services in Tanzania. There is no doubt that mobile money emerged at a time when financial exclusion was a major issue, and that the advent of mobile money was opposed by the banks who thought that it was entering the money business, and that the banks were in a better position to do money business better than any other institutions. For this reason, it is crucial to understand the development of mobile money and the politics of financial inclusion that allowed it to succeed. I have chosen the case study of Tanzania because not only that mobile money has thrived there, but also mobile money as we perceive it today was firstly invented by the e-Fulusi, a Tanzanian company, and failed before it was relaunched in Kenya by MPesa and succeeded. Moreover, the development of mobile money and the politics of financial inclusion have proven their importance in fighting financial exclusion and in increasing access to formal financial services for the poor, which is key to economic growth and poverty alleviation.